al-'Abbasiyyun wa-atharuhum al-mi'mariyah fi al-'Iraq wa Misr wa Afriqiya - 'Abduh, Abd Allah Kamil Musa. (al-Qahirah : Dar al-Afaq al-'Arabiyah, 2002)
Islamic architecture; Abbasids; Islamic empire; history; 750-1258.
Bibliography : 233-242.
Keywords: Islamic architecture -- History; Islamic architecture -- Africa -- History; Islamic architecture -- Egypt -- History; Islamic architecture -- Iraq -- History